Validity and Reliability of the Questionnaire for Assessing Women’s Reproductive History in Azar Cohort Study - Pezeshki, Mohammad Zakaria (J Caring Sci, 2017)
This study was done to evaluate the validity and reliability of women’s reproductive history questionnaire which will be used in Azar Cohort study; a cohort that is conducted by Tabriz University of Medical Science in Shabestar county for identifying risk factors of no communicable diseases. Content and face validity were evaluated by ten experts in the field and quantified as content validity index (CVI) and content validity ratio (CVR). To assess the reliability, using test-retest approach, kappa statistic was calculated for categorical variables and intra-class correlation coefficient (ICC) was used for the quantitative items. The calculated CVI and CVR were 0.91and 0.94, respectively. Reliability for all items was high. The ICC was 0.99 and kappa statistic was equal to 1. The final version of questionnaire was redesigned in 26 items with 7 subscales.